Mark Up Optimum, Keuntungan Dan Probabilitas Menang Tender Pada Proyek Konstruksi - Aldrin, Muhammad Daviendra Maulana; Suraji, Akhmad (Jurnal Bangunan, Konstruksi & Desain, 2024)
Determining the bid price in a construction project tender is faced with a trade-off between the optimum markup value, expected profit and the chance of winning the tender. This research aims to report the research results on the best offer price strategy model. This research was carried out by analyzing secondary data on building work tender package prices in DKI Jakarta Province. The data analysis used the Friedman and Gates method with a single and multiple normal distribution statistical approach. Friedman and Gates model calculations are discussed in this research. This paper also discusses the trade-off between markup and profit and the probability of winning a tender based on the project value category. This research shows that the Friedman Model is better used for project sizes of 1 - 10 billion Rupiah, while the Gates Model and Friedman Model produce the same output for project sizes of IDR 15 - 50 billion and greater than IDR 50 billion. Based on this, the results of this research can be used to determine the optimum bid price according to the amount of markup and probability of winning.